2019
DOI: 10.1002/jcla.23133
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of telomere length and telomerase reverse transcriptase variant (rs2242652) on the multiple myeloma patients

Abstract: Background The search for enhancement of multiple myeloma prognostic tools is an area of current research. This study aimed to assess the clinicopathological impact of telomere length and telomerase reverse transcriptase (TERT) polymorphic variant, rs2242652, on multiple myeloma (MM) patients. Methods Fifty MM patients and 50 healthy controls were included. Relative telomere length (RTL) and rs2242652 genotype polymorphic variants of TERT were analyzed using real‐time polymerase chain reaction (PCR). The MM pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In addition, miRNAs were negatively correlated with LDH (P < .05) in MM. These serum parameters reflecting the tumor load of MM, not only relate to the clinical stage, but also affect the renal function and prognosis of MM patients [27][28][29]. In our previous study, we demonstrated that these serum indicators were related to MM prognosis 30.…”
mentioning
confidence: 86%
“…In addition, miRNAs were negatively correlated with LDH (P < .05) in MM. These serum parameters reflecting the tumor load of MM, not only relate to the clinical stage, but also affect the renal function and prognosis of MM patients [27][28][29]. In our previous study, we demonstrated that these serum indicators were related to MM prognosis 30.…”
mentioning
confidence: 86%
“…MM patients have longer telomeres compared to the control [ 92 , 93 ]. In MM, a higher TERT amplification was detected and presented a significant association with poor prognosis of the disease [ 94 ].…”
Section: Novel Biomarkers For Diagnosis and Prognosis Of MMmentioning
confidence: 99%